The extent of pericardial involvement evaluated by cardiac MRI in patients with ST-Segment elevation myocardial infarction: predictors and outcomes. (25th November 2020) - Massalha, E; Di Segni, E.L.I.O; Fardman, A; Younis, A; Brodov, Y; Hersckovici, R; Mazin, I; Beigel, R; Matetzky, S; Goitein, O
Abstract: Background: The clinical diagnosis of peri-myocardial infarction pericarditis declined dramatically in the era of primary PCI and novel antiplatelet agents. However, recent data documents the presence of pericardial effusion in substantial proportion of acute MI patients, while recent randomized trial showed that anti-inflammatory drugs seem to improve cardiovascular outcomes, although the mechanism of the benefit remains uncertain. Methods: We prospectively evaluated 187 consecutive patients, without known prior coronary disease, who underwent primary PCI for STEMI. All patients underwent cardiac MRI (CMR) on day 5±1 post admission. CMR was performed using a 1.5 T (n=101) and 3 T (n=86) scanners. Delayed enhancement (DE) and microvascular obstruction (MVO) were quantified as % of the left ventricular mass (LV). The presence of DE and MVO was recorded according to the AHA segments model. DE was also qualitatively assessed for the degree of transmurality in each segment. CMR pericarditis was defined as evidence of pericardial enhancement on DE images. The presence of pericardial effusion was also documented. Pericarditis extent was expressed as the number of pericardial segments with increased DE. Major adverse cardiac events were defined as the composite of death, recurrent myocardial infarction, stroke, urgent revascularization and hospitalization due to either heart failure or bleeding during the first year following STEMI. Results: Pericardial effusion was found in 94 patients (50%) and enhancement of the pericardium on DE images in 120 patients (65%). In contrary, a clinical diagnosis of peri-myocardial infarction pericarditis was documented and anti-inflammatory therapy was initiated only in three patients (1%). A significant positive correlation was demonstrated between pericardial involvement and either quantitative or qualitative assessment of DE (p<0.001, r=0.34) and MVO (p<0.001, r=0.282). DE transmurality (per segment) was associated with both location of pericardial involvement and its extent (p<0.001). A multivariate logistic regression analysis revealed that DE extent and MVO were independent predictors of pericardial involvement (OR 1.07; CI 95% 1.06–1.13, p=0.02 and OR 1.29; CI 95% 1.01–1.64, p=0.04 for DE and MVO respectively). Additional parameters that were associated with CMR diagnosis of pericarditis included higher maximal CRP levels and proximal coronary lesions. The 1-year incidence of major adverse events was similar in patients with or without CMR-defined pericarditis. Conclusions: In contrast to the low rate of clinically diagnosed pericarditis, CMR documented pericardial involvement in more than 65% of STEMI patients. This finding is independently associated with the extent and degree and location of myocardial damage. Funding Acknowledgement: Type of funding source: None